A novel semi-analytical method for notch stress and fatigue strength analysis of tube-flange welded joints. (December 2020) - Hu, Yaoyu; Yan, Renjun; Shen, Wei; Berto, Filippo; Li, Chunmei
Graphical abstract: Tube-flange structures are widely used in pipeline engineering and ocean engineering. Complex bending and torsional stresses are carried at the transition position of tube-flange joints, which is the key position of crack initiation and propagation. In order to simplify the fatigue assessment process of tube-flange welded joints, a semi-analytic method of notch stress was presented to rapidly estimate the notch stress around the weld toe in engineering. Meanwhile, the corresponding relations between singular intensity factor, notch stress intensity factor, strain energy density and equivalent peak stress were further deduced based on the proposed equivalent singular intensity factors. Moreover, the evaluation results obtained by the simple formula and the results obtained by the traditional methods are comprehensively compared. The results show that the fatigue assessment parameters calculated by the traditional approaches and the proposed method are in good agreement. Highlights: A novel semi-analytical method for notch stress and fatigue strength analysis of tube-flange welded joints was proposed. The proposed semi-analytic stress formula was determined by the stress distribution rather than the peak stress. A rapid method to determine ZP, NSIF, local SED and peak stress was further presented. Abstract: This paper presents a semi-analytic method to rapidly estimate the notch stress and fatigue strength for tube-flange welded joints. Considering the stress singularity effect at the weld toe, the parameters related to geometry and opening angle are simplified as singular intensity factors. The equivalent singular intensity factors can be fitted by the stress distribution rather than the peak stress at the corner. On this basis, the modified notch stress formulas for tube-flange welded joint (TFWJ) under pure bending or torsion load were fitted and verified. Meanwhile, the simple relationships between singular intensity factor, notch stress intensity factor, strain energy density and peak stress were further deduced, separately. The comparison results show that the fatigue assessment parameters calculated by the traditional approaches and the proposed method are in good agreement. Finally, four groups of fatigue data of TFWJs were summarized to verify the simplified assessment formulas.